Pengaruh Lama Fermentasi Dedak Gandum Terhadap Kandungan Asam Fitat Serta Kecernaan In Vitro Bahan Kering dan Bahan Organik - Mbali, Rambu Yow; Mullik, Marthen L.; Oematan, Gustaf (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aimed to determine the effect of the duration of wheat bran fermentation on phytate acid content, in vitro dry matter digestibility, and organic matter digestibility. The method used in this study was a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications, resulting in 16 experimental units. The treatments were as follows: LF0: without fermentation (control), LF2: fermentation for 2 days, LF4: fermentation for 4 days, and LF6: fermentation for 6 days. The mixture of the research material before fermentation was wheat bran mixed with an inoculum solution at a ratio of 1:1. The inoculum was made from a mixture of 15 liters of clean water, 30 ml of EM4, 100 ml of liquid palm sugar, and 100 ml of fresh cow dung fluid taken from cows fed with fresh leucaena leaves and grass. The variables measured in this study were phytate acid content, dry matter digestibility (DMD), and organic matter digestibility (OMD). The results of the statistical analysis showed that the treatments had a very significant effect (P=0.01) on the phytate acid content, dry matter digestibility (DMD), and organic matter digestibility (OMD) of fermented wheat bran. The total phytate acid content value in LF0 was 0.48%, which decreased to 0.28% in LF6, dry matter digestibility in LF0 was 69.75% and increased to 74.98% in LF2, and organic matter digestibility in LF0 was 70.19% and increased to 75.56% in LF6. Based on the research results, it can be concluded that wheat bran with different fermentation durations using fresh cow dung can reduce phytate acid content and increase dry matter digestibility and organic matter digestibility in wheat bran.